Cytoplasmic TDP-43 leads to early functional impairments without neurodegeneration in a Serotonergic Neuron-Specific C. elegans Model - Lacour, Ailin (2026)
TDP-43 proteinopathies, such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), are marked by the pathological cytoplasmic accumulation of TAR DNA-binding protein 43 (TDP-43), leading to progressive neuronal dysfunction and degeneration. To investigate the early functional consequences of TDP-43 mislocalization, we generated Caenorhabditis elegans models expressing either wild-type human TDP-43 or a variant with a mutated nuclear localization signal (ΔNLS), specifically in serotonergic neurons. These neurons were chosen because in C. elegans they regulate well-characterized behaviors, providing a straightforward readout of neuronal function. We found that expression of either TDP-43 variant impaired serotonin-dependent behaviors—including pharyngeal pumping, egg-laying, and locomotion slowing upon food encounter—with the cytoplasmic ΔNLS form causing more severe deficits. These behavioral impairments are evident even while the serotonergic neurons remain apparently normal in structure, suggesting that neuronal dysfunction precedes overt neurodegeneration. Moreover, the serotonergic HSN neurons that control egg-laying were also partially responsive to the selective serotonin reuptake inhibitor fluoxetine, suggesting that neurotransmitter release remains functional to some extent. Altogether, our findings demonstrate that TDP-43 expression causes neuronal dysfunction leading to behavioral deficits, even in the absence of detectable structural pathology and that its mislocalization to the cytoplasm results in more severe behavioral impairments. This C. elegans model provides a genetically tractable system to dissect early mechanisms of TDP-43-mediated neuronal dysfunction and to identify therapeutic strategies targeting predegenerative stages of ALS/FTD